A Healthy Game-Theoretic Evaluation of NATO and Indonesia's Policies in the Context of International Law - Rita Komalasari; Cecep Mustafa (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
This study examines the policies of two prominent actors, the North Atlantic Treaty Organization (NATO) and Indonesia while considering their adherence to international law. The analysis is conducted through the lens of game theory, which provides a framework for evaluating strategic interactions in the cyber domain. This study aims to explore how game theory can be applied to assess the policies of NATO and Indonesia in combating and to establish the link between game-theoretic evaluation and conflict resolution in Indonesia's cyber landscape. By understanding strategic interactions and motivations of various actors, this study seeks to provide insights into fostering international cooperation, promoting responsible state behavior, and enhancing cybersecurity. This study employs a qualitative research design, relying on literature reviews, policy analyses, and case studies to examine the cybersecurity policies of NATO and Indonesia. Game theory serves as the primary analytical framework to model cyber conflicts and interactions between different actors. The policies of NATO and Indonesia are evaluated concerning cooperation, competition, and compliance with international law. The analysis reveals that both NATO and Indonesia employ distinct approaches to combating. NATO's collective response emphasizes coordination, information sharing, and cooperative defense strategies, reinforcing international cybersecurity efforts. On the other hand, Indonesia's response is shaped by its unique challenges and priorities, leading to tailored policies and collaborations. Game-theoretic evaluation establishes the importance of cooperation, deterrence, and adherence to international law in resolving conflicts arising from cyber threats in Indonesia. This research highlights the significance of international partnerships, capacity building, and context-specific best practices for a more secure digital environment in Indonesia and beyond. Ultimately, game-theoretic evaluation proves instrumental in shaping effective cybersecurity strategies and promoting responsible behavior in the ever-evolving cyber landscape.